2023
DOI: 10.1126/science.ade1105
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of CaMKIIδ oxidation by CRISPR-Cas9 base editing as a therapy for cardiac disease

Abstract: CRISPR-Cas9 gene editing is emerging as a prospective therapy for genomic mutations. However, current editing approaches are directed primarily toward relatively small cohorts of patients with specific mutations. Here, we describe a cardioprotective strategy potentially applicable to a broad range of patients with heart disease. We used base editing to ablate the oxidative activation sites of CaMKIIδ, a primary driver of cardiac disease. We show in cardiomyocytes derived from human induced pluripotent stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 38 publications
(58 reference statements)
1
66
0
Order By: Relevance
“…However, significant neurologic side effects, including seizure activity, were reported after administration of Ru265 in vivo 56 and the in vivo efficacy of other inhibitors remains to be determined. As an attractive alternative, Crispr/Cas9 technology has been recently deployed to selectively ablate activated CaMKII 57 . Given that mitochondrial Ca 2+ entry is ubiquitous, effective use of any of these nascent tools for prevention of neointima formation would require the development of delivery strategies that are selective for VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, significant neurologic side effects, including seizure activity, were reported after administration of Ru265 in vivo 56 and the in vivo efficacy of other inhibitors remains to be determined. As an attractive alternative, Crispr/Cas9 technology has been recently deployed to selectively ablate activated CaMKII 57 . Given that mitochondrial Ca 2+ entry is ubiquitous, effective use of any of these nascent tools for prevention of neointima formation would require the development of delivery strategies that are selective for VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, gene therapy approaches to restore physiological SR Ca 2+ reuptake, although promising in preclinical models [ 93 ], have failed to produce results in HF patients [ 94 , 95 ]. Encouraging results, however, were published very recently by Lebek et al showing that CRISPR-Cas9 base editing to ablate the oxidative activation sites of CaMKIIδ was effective in protecting the heart from ischemia-reperfusion damage in mouse models [ 96 ].…”
Section: Nuclear Ca 2+ Dysregulationmentioning
confidence: 99%
“…Examination of patient samples from these trials revealed poor viral infection of myocardium. In contrast to the CUPID trials, Lebek and colleagues opted for intramyocardial injection delivery, which is considered to lead to higher retention of injectate . However, intracardiac delivery has been mired with proarrhythmic adverse effects in human and primate trials exploring stem cell therapy, and importantly, these adverse effects were underappreciated in small animal models .…”
mentioning
confidence: 99%
“…Altogether, Lebek and colleagues provide an elegant strategy for preventing CaMKII-dependent injury in ischemia/reperfusion. Their study further cements CaMKII as a pivotal cardiac therapeutic target and provides valuable insight into the feasibility of CaMKII inhibition postinjury.…”
mentioning
confidence: 99%
See 1 more Smart Citation